The immunotherapeutic role of indoleamine 2, 3‐dioxygenase in head and neck squamous cell carcinoma: A systematic review. (30th May 2021) - Lin, Daniel J.; Ng, James C. K.; Huang, Lei; Robinson, Max; O'Hara, James; Wilson, Janet A.; Mellor, Andrew L.
Abstract: Background: Novel cancer immunotherapy seeks to harness the body's own immune system and tip the balance in favour of antitumour activity. The intracellular enzyme indoleamine 2, 3‐dioxygenase (IDO) is a critical regulator of the tumour microenvironment (TME) via tryptophan metabolism. The potential immunotherapeutic role of IDO in head and neck squamous cell carcinoma (HNSCC) requires further exploration. We aim to assess the evidence on IDO in HNSCC. Methods: A systematic review of literature and clinical trials databases. Results: We included 40 studies: seven involved cell lines: eight assessed tumour immunohistochemistry: ten measured IDO gene transcription: 15 reported on clinical trials. Increased cell line IDO expression was postulated to adversely affect tumour metabolism and apoptosis. Immunohistochemical IDO expression correlated with worse survival. Gene transcription studies associated IDO with positive PD‐L1 and human papillomavirus (HPV) status. Phase I/II clinical trials showed (a) overall response (34%‐55%) and disease control rates (62%‐70%) for IDO1 inhibitor in combination with a PD‐1 inhibitor, (b) similar safety profiles when both are used in combination therapy compared to each as monotherapies and (c) IDO gene expression as a predictive biomarker for response to PD‐L1 therapy. Conclusions: IDO expression is increased in the TME of HNSCC, which correlates with poor prognosis. However, the exact mechanism of IDO‐driven immune modulation in the TME is an enigma. Future translational studies should map IDO activity during HNSCC treatment and elucidate its precise role in the TME, such research will underpin the development of clinical trials establishing the efficacy of IDO inhibitors in HNSCC.